Synthesis and characterization of cellulose nanocrystals/Gd2O3 nanocomposite as a dual-mode contrast agent for MRI via gamma-ray irradiation - Whba, Fathyah; Mohamed, Faizal; Whba, Rawdah; Idris, Mohd Idzat; Mohd Noor, Noramaliza; Mahmood, Mohamad Khiari (Elsevier, 2024)
This study developed a biocompatible nanocomposite using cellulose nanocrystals (CNCs), polyethylene glycol (PEG), and sodium hydroxide (NaOH), combined with gadolinium oxide nanoparticles (Gd2O3-NPs) through gamma radiation to decrease the size of nanoparticles and increase their uniformity. This research found that the (CNCs-PEG/NaOH)/Gd2O3 nanocomposite exhibits notable characteristics, including high saturation magnetization (1.44 emu/g), remarkable colloidal stability with a highly negative surface charge of −31.4 mV, and a small hydrodynamic size of 5.5 ± 0.7 nm. Furthermore, the MTT assay conducted on HeLa cell lines revealed the excellent biocompatibility of the (CNCs-PEG/NaOH)/Gd2O3 nanocomposite. No cytotoxic effects were observed, and the nanocomposite exhibited adequate cellular uptake. Moreover, the (CNCs-PEG/NaOH)/Gd2O3 nanocomposite displayed a remarkable enhancement effect on both T1 and T2-weighted images, with high r1 and r2 relaxivity values of 21.694 mM−1 s−1 and 43.799 mM−1 s−1, respectively, resulting in a relaxivity ratio (r2/r1) of 2.02 when compared to clinical and commercial agents. This biocompatible nanocomposite holds promise as a dual contrast agent in MRI and various other biomedical applications. It is envisaged that gamma irradiation is a good method to produce nanoparticles within the nanoscale range. © 2024 Elsevier Ltd